2019
DOI: 10.1007/s00410-019-1618-y
|View full text |Cite|
|
Sign up to set email alerts
|

Phosphorus and aluminum zoning in olivine: contrasting behavior of two nominally incompatible trace elements

Abstract: Phosphorus zoning in olivine is receiving considerable attention for its capacity to preserve key information about rates and mechanisms of crystal growth. Its concentration can vary significantly over sub-micron spatial scales and form intricate, snowflake-like patterns that are generally attributed to fast crystal growth. Ostensibly similar aluminum enrichment patterns have also been observed, suggesting comparable incorporation and partitioning behavior for both elements. We perform 1-atm crystallization ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 78 publications
2
52
0
Order By: Relevance
“…First, we test the hypothesis that lattice distortions are produced during an early phase of branching dendritic growth, followed by textural reequilibration during periods of reduced undercooling 5 . Due to a change in olivine-melt partitioning during rapid dendritic growth, high concentrations of phosphorous (P) are incorporated into the crystal structure 39 . While the external morphology of dendritic crystals evolves during subsequent textural reequilibration to obscure this early growth phase, slow diffusion rates preserve internal P enrichments 40 .…”
Section: Resultsmentioning
confidence: 99%
“…First, we test the hypothesis that lattice distortions are produced during an early phase of branching dendritic growth, followed by textural reequilibration during periods of reduced undercooling 5 . Due to a change in olivine-melt partitioning during rapid dendritic growth, high concentrations of phosphorous (P) are incorporated into the crystal structure 39 . While the external morphology of dendritic crystals evolves during subsequent textural reequilibration to obscure this early growth phase, slow diffusion rates preserve internal P enrichments 40 .…”
Section: Resultsmentioning
confidence: 99%
“…The present results show that growth rates estimated from 3D can attain these values without necessitating extreme undercooling conditions. A companion paper based on the same experiments (Shea et al, 2019) fully explores the consequences of rapid growth for P and Al, and shows that the boundary layer enrichment model works for certain elements like Al but not for P. Regardless of the peculiar behavior of P, the concentration of other elements is clearly affected by disequilibrium caused by rapid growth, which may even affect Fe-Mg contents in olivine (Figure 7). Our results relax the requirement for unrealistically large undercooling and may pave to way to better understanding the extent to which olivine major and trace element compositions can be controlled by disequilibrium processes.…”
Section: Growth Mechanisms and Consequences For Element Partitioning mentioning
confidence: 98%
“…It should be noted that aside from differences in experimental volumes and techniques used to estimate growth rates, the experimental strategy employed herein differs from that of Jambon et al (1992) in one major respect: they used closed melt inclusions as experimental vessels for olivine crystallization in order to isolate the process of growth from that of nucleation, while our olivine is allowed to grow "freely" in a much larger volume of melt. This strategy allowed them to explore growth even at high degrees of undercooling (− T = 150 • C), a region FIGURE 1 | (A) Temperature-fO 2 phase equilibria diagram calculated from MELTS using the Kīlauea 1820CE bulk composition at 1 atm (modified from Shea et al, 2019). Gray region shows the range in fO 2 imposed in the experiments.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…http://www.minsocam.org/ the coupled CaAl-NaSi substitution, and the slow intracrystalline diffusion of those species prevent compositional homogenization, thus compositional zoning is a proxy for the pressuretemperature-compositional history of a given plagioclase. This is in contrast to minerals with no major element sensitivity to those conditions, or those, like olivine, with fast internal diffusion that removes most major element compositional zoning (Shea et al, 2019).…”
Section: Introductionmentioning
confidence: 87%
“…http://www.minsocam.org/ Humphreys et al, 2006). Kawamoto (1992) shows that some patchy zoning in plagioclase may record initially skeletal habits, and Shea et al (2019) have shown that some euhedral olivine crystals form through infilling of initially skeletal growth.…”
Section: Introductionmentioning
confidence: 99%